Pengaruh Financial Knowledge, Financial Behavior Dan Financial Attitude Terhadap Personal Financial Management Pada UMKM - Yusril Ramdani; Indah Ariffianti; Baiq Desthania Prathama (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
The variables of this study consist of 4 (four) independent variables, namely financial knowledge (X1), financial behavior (X2), financial attitude (X3) and the dependent variable, namely personal financial management (Y). The population of this study is 173 small and medium-sized business actors in Desa gili Indah, Kabupaten Lombok Utara (KLU), the criteria for this study are respondents who have a business and have a net income of around 1-2 million and 2 million and above. The sampling technique was probability sampling with the proportionate stratified sampling method and found that the number of respondents was 63 respondents using a questionnaire. The multiple linear regression analysis method was processed using SPSS version 25. The results in this study showed that financial knowledge had no significant effect on personal financial management, financial behavior had a significant effect on personal financial management, financial attitude had no significant effect on personal financial management and the results of simultaneous tests showed that independent variables (financial knowledge, financial behavior, and financial attitude) had a significant influence on personal financial management.